Factors associated with unrealized fertility among women approaching the end of reproductive age in sub-Saharan Africa - Tsion Mulat Tebeje; Mesfin Abebe; Achamyeleh Birhanu Teshale; Mekonnen Birhanie Aregu (PLoS ONE, 2025)
Background Understanding women’s fertility preferences is essential for addressing reproductive behaviors and family planning needs. In sub-Saharan Africa, fertility rates remain high, yet many women experience unrealized fertility, which is having fewer children than desired. However, the factors influencing unrealized fertility remain underexplored. This study assessed the determinants of unrealized fertility among women approaching the end of their reproductive years in sub-Saharan Africa. Methods A secondary data analysis was conducted using phase eight Demographic and Health Surveys data from 19 sub-Saharan African countries. The weighted sample included 46,408 women aged 40–49 years. A multilevel Poisson regression model with robust variance was used to identify factors associated with unrealized fertility. Adjusted prevalence ratios with 95% confidence intervals (CI) were reported, and variables with a p value <0.05 were considered statistically significant. Results The pooled prevalence of unrealized fertility among women aged 40–49 years was 61.43% (95% CI: 57.63%, 65.24%). Rwanda (37.40; 95% CI: 27.92%, 46.88%) and Sierra Leone (69.34; 95% CI: 60.30%, 78.38%) had the lowest and highest prevalence, respectively. Older maternal age at first birth, being employed, having no children or only children of one sex, and experiencing child death were associated with higher prevalence of unrealized fertility. Conversely, higher maternal education, the use of contraceptives, having both male and female children, and residing in rural areas were associated with lower prevalence of unrealized fertility. Conclusions A large proportion of women nearing the end of their reproductive careers in sub-Saharan Africa have experienced unrealized fertility. Therefore, addressing cultural norms surrounding sex preference and number of children, alongside empowering women through improved access to education, healthcare, and comprehensive sexual and reproductive health services, is critical.